Short interpregnancy interval and its predictors in Ethiopia: implications for policy and practice. - Mruts, Kalayu; Tessema, Gizachew; Kassaw, N.A.; Gebremedhin, Amanuel; Scott, Jane; Pereira, Gavin (2022)
Introduction: interpregnancy interval (IPI) is the time elapsed between the birth of one live child and the conception of subsequent pregnancies. Several studies in Ethiopia indicated a high prevalence of a short interbirth interval - a proxy indicator of IPI. However, these studies were prone to selection bias as they did not include women who did not go on to have another pregnancy. Therefore, this study estimated the incidence of short IPI (< 24 months) and its risk factors among women who had at least one child in Ethiopia.